C-Proeq algorithm for Subcarrier Allocation for WiMAX (Global Journals of Research in Engineering, 2011)
WiMAX is one of the latest techniques for providing Broadband Wireless Access in metropolitan area. Phenomenal growth in the demand for higher bandwidth increases the importance of subcarrier allocation. WiMAX uses OFDMA techniques based on multiuser diversity such as Adaptive Modulation Coding. Resource Allocation Algorithm improves performance based on user channel condition. Fair Allocation Algorithm maximizes the minimum data rate and allocates equal bandwidth to all users. However this allocation reduces the bandwidth efficiency of the system. In order to overcome this drawback Heuristics allocation such as Proportional Allocation and Equal Capacity Increment are proposed. To improve their performance, both allocations are combined and C-Proeq (Combination of Proportional and Equal capacity increment algorithms) is proposed. The other objective is to share better trade off between bandwidth efficiency and fairness. Performance has been compared on the basis of bit error rate with respect to signal to noise ratio and various user distances from base station.
Keywords: Adaptive Modulation Coding; Subcarrier allocation; WiMAX OFDMA